The C8ORF38 homologue Sicily is a cytosolic chaperone for a mitochondrial complex I subunit. - Zhang, K.; Li, Z.; Jaiswal, M.; Bayat, V.; Xiong, B.; Sandoval, H.; Charng, W.L.; David, G.; Haueter, C.; Yamamoto, S.; Graham, B.H.; Bellen, H.J. (Journal of Cell Biology, 2013)
Mitochondrial complex I (CI) is an essential component in energy production through oxidative phosphorylation. Most CI subunits are encoded by nuclear genes, translated in the cytoplasm, and imported into mitochondria. Upon entry, they are embedded into the mitochondrial inner membrane. How these membrane-associated proteins cope with the hydrophilic cytoplasmic environment before import is unknown. In a forward genetic screen to identify genes that cause neurodegeneration, we identified sicily, the Drosophila melanogaster homologue of human C8ORF38, the loss of which causes Leigh syndrome. We show that in the cytoplasm, Sicily preprotein interacts with cytosolic Hsp90 to chaperone the CI subunit, ND42, before mitochondrial import. Loss of Sicily leads to loss of CI proteins and preproteins in both mitochondria and cytoplasm, respectively, and causes a CI deficiency and neurodegeneration. Our data indicate that cytosolic chaperones are required for the subcellular transport of ND42.